Augmenting television narratives using interactive home appliances. Issue 1 (2nd January 2022) - Hong, Jiwoo; Lee, Woohun
ABSTRACT: This study focuses on the use of everyday objects as new media for enriching digital storytelling experiences, especially as they pertain to viewing television narratives in living room environments. Through a design ideation workshop, we develop a strategy for augmenting television narratives using interactive home appliances. The ideas obtained through the workshop revealed that interactive home appliances connected to television systems can serve as both input and output channels capable of delivering narrative elements as additional output and can support active viewer engagement in narrative manipulation. Another strategy involved mirroring the environments of television narratives with the physical world to enable spatial immersion into such narratives. Based on the strategies, we discuss the criteria valued by the designers when it comes to designating interactions between home appliances and television narratives and the critical aspects that should be considered in further configurations and applications of such strategies.